2022
DOI: 10.1108/ilt-09-2021-0376
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation in oscillatory porous squeeze film: a numerical approach

Abstract: Purpose This study aims to present a numerical model to investigate cavitation effects on oscillatory porous squeeze film. This effect is able to cause considerable damage to the lubrication mechanisms, mainly in the form of surface erosion. The erosion process is caused by surface spalling due to alternating positive and negative contact stresses imposed by bubble collapse. If the process continues uncontrolled, the performance of the contact will rapidly deteriorate. Design/methodology/approach The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…They found that, if viscoelastic effects increase, then the cavitation region widens until reaching a value of Weissenberg number for which a full-film reformation does not occur after the initial film rupture. Recently, Sobhi et al (2022) presented a numerical model to study the effects of cavitation on an oscillating isotropic porous squeeze film lubricated by a Newtonian fluid. Their numerical results show that frequency, amplitude and permeability have a significant influence on cavitation generation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that, if viscoelastic effects increase, then the cavitation region widens until reaching a value of Weissenberg number for which a full-film reformation does not occur after the initial film rupture. Recently, Sobhi et al (2022) presented a numerical model to study the effects of cavitation on an oscillating isotropic porous squeeze film lubricated by a Newtonian fluid. Their numerical results show that frequency, amplitude and permeability have a significant influence on cavitation generation.…”
Section: Introductionmentioning
confidence: 99%